Electrical Characterizations of Polypyrrole Thin Film Deposited on Glass Surfaces by Using the LCR Meter - Syamimi, N.; Yahud, S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The electrical characterization of Polypyrrole (PPy) thin films is investigated as a function of various thin film thickness. Ten sets of uniform PPy thin films with different layers were prepared by using the spin coating method applied on glass substrates treated with oxygen plasma. The electrical resistance, inductance, conductance of the films was observed as a function of film thickness at room temperature. These parameters have been measured by using the LCR meter. The behavior of the PPy thin film’s resistance was then interpreted in terms of resistivity and conductivity. The results showed that as the thickness of the thin film increase, the resistivity decrease thus increasing its conductivity.